Regulatory Reform of Mental Health Services in Indonesia: Legal and Human Rights Perspectives - Gevan Naufal Wala (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Mental health is an integral component of health that is often overlooked in Indonesia's healthcare system. This research analyzes the regulatory framework of mental health services in Indonesia from legal and human rights perspectives. Using normative juridical research methods with statutory and conceptual approaches, this study examines various legal instruments related to mental health services, identifies regulatory gaps, and formulates necessary reform directions. The results indicate that existing regulations have not fully accommodated human rights principles in mental health services, particularly regarding accessibility, service quality, and patient rights protection. There is an urgent need for comprehensive regulatory reform to strengthen legal protection, improve service access, and ensure respect for the human rights of people with mental health conditions. Such reform must include regulatory harmonization, strengthening oversight mechanisms, and developing rights-based service standards.